An underlying mechanism of change: How prostate cancer survivors make sense of dietary changes? - Kassianos, Angelos P.; Raats, Monique (My University, 2013)
Background. Dietary behaviour and actions are ibelieved to be influenced by both social and personal factors while how breast cancer survivors make sense of their relationship with food is believed to be divided into stages. The aim of this study is to explore how prostate cancer survivors make sense of any changes in their diet after diagnosis. Methods. This is a Qualitative study using semi-structured interviews with 8 men diagnosed with prostate cancer and analyzed using Thematic Analysis. Findings. Overarching themes were “determinants ” and “perceived results of change”. Seven themes focusing on attitudes, beliefs and relationships explained the two overarching themes. We hypothesize that they form an underlying mechanism used by participants to determine and explain lifestyle change especially related to diet. Discussion. The processes of dietary change have a social, interpersonal and intrapersonal nature. The schema we suggest derives from how prostate cancer survivors make sense of meanings, experiences and relationships.